2022
DOI: 10.18063/ijb.v8i2.514
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Attachment and Collagen Type I Deposition of MC3T3-E1 Cells via Electrohydrodynamic Printed Sub-Microscale Fibrous Architectures

Abstract: Micro/sub-microscale fibrillar architectures of extracellular matrix play important roles in regulating cellular behaviors such as attachment, migration, and differentiation. However, the interactions between cells and organized micro/sub-microscale fibers have not been fully clarified yet. Here, the responses of MC3T3-E1 cells to electrohydrodynamic (EHD) printed scaffolds with microscale and/or sub-microscale fibrillar architectures were investigated to demonstrate their potential for bone tissue regeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Recently, electrohydrodynamic (EHD)-printed microfibrous scaffolds were developed for tissue engineering applications due to their unprecedented advantages for generating cell-favorable microenvironments [20][21][22]. It is reported that EHD-printed PCL scaffolds with specifically designed microscale fibers and pores can enhance cellular activities, including alignment [23], adhesion, proliferation and migration [24]. However, the absence of stem cells at the wound locations remains one of the main causes of the failure of rotator cuff healing [19,25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, electrohydrodynamic (EHD)-printed microfibrous scaffolds were developed for tissue engineering applications due to their unprecedented advantages for generating cell-favorable microenvironments [20][21][22]. It is reported that EHD-printed PCL scaffolds with specifically designed microscale fibers and pores can enhance cellular activities, including alignment [23], adhesion, proliferation and migration [24]. However, the absence of stem cells at the wound locations remains one of the main causes of the failure of rotator cuff healing [19,25].…”
Section: Introductionmentioning
confidence: 99%
“…In this aspect, tiny fibers derived from electrohydrodynamic (EHD) jetting (e.g. EHD printing, electrospinning) are recognized as important building blocks for mimicking the fibrillar nature of ECM [10][11][12]. In one interesting study, Huang et al [13] developed macroscale polycaprolactone (PCL) scaffolds with both microscale and nanoscale filaments by alternately using FFF and electrospinning techniques in a layer-by-layer manner.…”
Section: Introductionmentioning
confidence: 99%